Education Model of Tarekat Based Islamic Boarding School and Its Influence on Modern Society - Mujiburrohman, Mujiburrohman; Saepudin, Didin; Alfelahi, Ismail Abdullah H. (JURNAL INDO-ISLAMIKA, 2024)
This study examines tarekat and its development in the Islamic education curriculum at Jagat Arsy Islamic Boarding School and how it affects modern society from the development of the educational model applied to it. The method used in this research is a qualitative approach, using data from observation, interviews, and documentation. The study results show that integrating tarekat into the curriculum of Islamic religious education has significant benefits, especially in developing spirituality and morality. Tarekat helps to increase self-discipline, closeness to God, and the formation of a better-centered character. However, challenges during its implementation, including resistance from conservative factions and the struggle to develop a standardized curriculum, hindered the process. The tarekat-based education model is perceived to have shifted public opinion regarding tarekat's adaptability to modern life, leading to increased support and adoption of tarekat practices. These findings reaffirm the significance of integrating tarekat into the education system and offer fresh insights for developing a comprehensive and systematic Islamic educational model.